Pengaruh Literasi Keuangan Terhadap Penggunaan Digital Payment Pada Mahasiswa Fakultas Ekonomi Uki Toraja - Stefani Marina Palimbong; Elisabet Pali; Astriwati Biringkanae; Randi Tangdialla (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to examine the effect of financial literacy on the use of digital payment shopee paylaters among Uki Toraja Faculty of Economics students. This research is a quantitative research with a survey method. The population in this study were all students of the Uki Toraja Faculty of Economics. With a total sample of 33 respondents who were selected using the Random Sampling technique. Based on the results of the study it can be concluded that financial literacy has a positive effect on the use of digital payment shopee paylater among Uki Toraja Faculty of Economics students with an influence level of 26.6%, while the remaining 73.4% is influenced by other variables not included in this study